Safe motherhood practice and maternity health in rural development (A case study of Diyalekharka Village, Dolakaha District). - Koirala, Ramila (2008)
ABSTRACT: The study entitled ''Safe Motherhood practice and Maternity Health in Rural Development'' in Diyalekharka Village of Dolkha district, on the basis of primary data collection for which field survey was conducted in Aug, 2008. 40 households were selected for study. Questionnaire was the major tools of data collection. Reproductive age (15-49) group's women and currently married who have at least one child at the time of survey were the respondent of the study. The study found that Diyalekharka villagers are socio-economically and educationally very poor. Their educational and economic condition seems pathetic. 67.5 percent respondent mothers are illiterate and cent percent mothers are engaging in housework. Similarly their practice in safe motherhood is dreadful. Age at marriage and child bearing age are satisfactory but 47.5 percent households had no access to the toilet facility. They don't use any contraceptives except 3 months Depo Provera injection for the purpose of family planning. Similarly they have no knowledge about abortion, which is indirectly affecting the health of mothers. 42.5 percent respondent mothers never listen about mobile clinic, 52.5 percent women haven't received antenatal service during pregnancy due to lack of knowledge. So they have no knowledge about the importance of ANC visit. They go for check up only when they feel any problem. Another main problem is that, about 40 percent respondent mothers were smoking, 22.5 percent drink alcohol and 10 percent mother eat mud during pregnancy which is directly affecting the health of mother and child. About the natal care, cent percent of deliveries are conducted at home setting with the assistance of family members. They wait for delivery till 2-3 days and they have strong belief in Dhami Jhankri. Similarly, post-natal care is not satisfactory. Only 22.5 percent mothers have taken post natal service and the remaining are debarred from it, Resting time of mothers is very poor in post delivery period. The overall observation and finding of the study shows that they practice of mother and child care is very poor due to their low educational and socio-economic status. They have traditional knowledge and practice to care themselves. Therefore, the result of research shows that immediate needs of education, awareness and income generating programmes are very essential for parents.